Validation of a Harmonized Enzyme-Linked-Lectin-Assay (ELLA-NI) Based Neuraminidase Inhibition Assay Standard Operating Procedure (SOP) for Quantification of N1 Influenza Antibodies and the Use of a Calibrator to Improve the Reproducibility of the ELLA-NI With Reverse Genetics Viral and Recombinant Neuraminidase Antigens: A FLUCOP Collaborative Study - Bernard, Marie-Clotilde; Waldock, Joanna; Commandeur, Sylvie; Strauß, Lea; Trombetta, Claudia Maria; Marchi, Serena; Zhou, Fan; van de Witte, Serge; van Amsterdam, Peter; Ho, Sammy; Hoschler, Katja; Lugovtsev, Vladimir; et al. (Frontiers in Immunology, 2022)
Current vaccination strategies against influenza focus on generating an antibody response against the viral haemagglutination surface protein, however there is increasing interest in neuraminidase (NA) as a target for vaccine development. A critical tool for development of vaccines that target NA or include an NA component is available validated serology assays for quantifying anti-NA antibodies. Additionally serology assays have a critical role in defining correlates of protection in vaccine development and licensure. Standardisation of these assays is important for consistent and accurate results. In this study we first validated a harmonised enzyme-linked lectin assay (ELLA)- Neuraminidase Inhibition (NI) SOP for N1 influenza antigen and demonstrated the assay was precise, linear, specific and robust within classical acceptance criteria for neutralisation assays for vaccine testing. Secondly we tested this SOP with NA from influenza B viruses and showed the assay performed consistently with both influenza A and B antigens. Third, we demonstrated that recombinant NA (rNA) could be used as a source of antigen in ELLA-NI. . In addition to validating a harmonised SOP we finally demonstrated a clear improvement in inter-laboratory agreement across several studies by using a calibrator. Importantly we showed that the use of a calibrator significantly improved agreement when using different sources of antigen in ELLA-NI, namely reverse genetics viruses and recombinant NA. We provide a freely available and detailed harmonised SOP for ELLA-NI. Our results add to the growing body of evidence in support of developing biological standards for influenza serology.